Intellectual property, free trade agreements and the United Kingdom : the continuing influence of European union law - Johnson, Phillip (Edward Elgar Publishing, 2021)
"Examining how trade agreements are interpreted both in trade tribunals and in the United Kingdom, this innovative book provides a well-rounded exploration of the numerous UK free trade agreements, including the UK-EU Trade and Cooperation Agreement, and their legal and policy implications for intellectual property. Providing a detailed assessment of the continuing role of EU standards in the UK, Phillip Johnson highlights how the UK has played an active role in shaping EU intellectual property law and policy. He explores the extent to which the UK's "new" trade agreements are tied to existing EU law and how this will preserve those standards in the UK, and how this might been received both nationally and globally. An extensive range of critical issues is covered, including copyright, patents, designs, trade marks, border control and technology transfer as well as featuring a calendar of EU laws which are replicated in the UK's current free trade agreements. This authoritative book will be an important source of reference for academics and practitioners seeking to understand the role of intellectual property law in UK and EU free trade agreements, as well as scholars and students of intellectual property, trade laws, and European Law"--